The effect of distance learning on the kanji reading ability of 4th semester students - Sara, Fransiska Niken; Diner, Lispridona (Japanese Research on Linguistics, Literature, and Culture, 2022)
Distance learning that works during the covid-19 pandemic changed the student's ability to receive or understand the learning content. Kanji is one of the difficult lecture materials for Japanese language students. A very large number of kanji letters and students' study habits are only made before a test becomes an obstacle in mastering kanji, so persistence, interest, and motivation are needed to learn kanji during distance learning. The preliminary study results show that students' motivation and interest decreased during distance learning. This study aims to determine whether there is an effect of distance learning on the ability to read kanji in fourth-semester students. The instrument used was a questionnaire distributed online with 47 students of Japanese Language Education class 2019 involved as respondents. The study results show that distance learning affects students' kanji reading skills by 22.4%. A student's ability to read kanji is influenced by external and internal factors, including a lack of support from friends and family during the study from home, lack of interest in learning kanji during distance learning, lack of time to practice and learn kanji every day, and students still tend to learn kanji only when there is an exam